Pengembangan Bahan Ajar Mata Kuliah Kewirausahaan pada Program Studi Pendidikan Seni Rupa Fakultas Seni dan Desain Universitas Negeri Makassar - Pangeran Paita Yunus; Satriadi Satriadi; Muhammad Muhaemin (Seminar Nasional LP2M UNM, 2022)
Abstract. The Entrepreneurship course is one of the compulsory subjects taught in the Fine Arts Education study program, Faculty of Art and Design, Makassar State University. After taking this course students are expected to be able to recognize their own potential, seek and create business opportunities, and have the courage to try entrepreneurship according to their abilities and the field they are in. In creating an entrepreneur, it can be started through entrepreneurship education taught in universities, but it will be faster if entrepreneurship education also begins to be applied from families, communities and educational institutions. This research will develop teaching materials for entrepreneurship courses and then measure the feasibility of teaching materials in terms of validity. This research refers to the development procedure developed by Borg & Gall which consists of ten steps that are systematically arranged, with easy-to-understand explanations, and can direct the developer from the beginning to the end of the research. In practice, it was only carried out up to the third step, namely from 1) preliminary study and data/information collection, 2) making plans, 3) developing initial drafts and validation tests or reviews by validators. The learning package components developed in this study are textbooks and media presentations. Entrepreneurship learning packages in the form of teaching materials and media presentations produced in this study are teaching materials that are appropriate for use in the learning process in Entrepreneurship courses in the Fine Arts Education Study Program, Department of Fine Arts and Crafts Education, Faculty of Art and Design, Makassar State University. This is because the teaching materials developed have met the validity criteria. Keywords: Development, Teaching Materials, Entrepreneurship